Syed Nawab Haider Naqvi. Development Economics: A New Paradigm, New Delhi: Sage Publications, 1993, 208 pages, Indian Rs 200.00. (The Pakistan Development Review, 1994)
With his well-known innovative intellectual skills, Syed Nawab Haider Naqvi has converted his several Presidential Addresses given at the Annual General Meetings of the Pakistan Society of Development Economists into a succinct and stimulating book. With its publication, Dr Naqvi has placed students of development economics in his debt for a lucid and systematic treatment of a subject which mainstream economists regard as a dying species, while the more knowledgeable ones, agreeing with Dr Naqvi, see it as very much alive though in need of revitalisation. Development economics, as a new paradigm or a distinct sub-discipline of economics, is only half-a-century old. The end of the Second World War saw the emergence of a new, independent but underdeveloped world with high expectations of quick prosperity. It was soon discovered, however, that mainstream economics was either neutral or unwilling to offer direct solutions to the serious problems that developing economies faced, particularly with regard to questions of alleviating widespread poverty and removing the abominably high income and wealth inequalities. It is against this background that development themes attracted the special attention of a large body of economists, who not only tried to analyse such themes theoretically with the help of the existing as well as new economic postulates but also offered vital remedies to solve the practical problems of under-development. In this way, development economics emerged as perhaps the best example of a synthesis between the positive and the normative aspects.